Re-configuring ancient greek music theory through technology: an adaptative electronic tuning system on a reconstructed ancient greek barbiton - Carlé, Martin; Georgaki, Anastasia (2011)
Background in Ancient Greek Music Theory and Philosophy. The foundation of musicology as a genuine discipline with a clear-cut subject matter and a well-defined terminology can be traced back to the writings of Aristoxenus of Taras, a pupil of Aristotle. However, its epistemological roots in harmonics and origin in Pythagorean philosophy reach back until the 6th century. Ad interim the development of a melodic notation system acted as a crucial factor to grow musicology into a ̔science’ of logical reasoning. Interestingly, and still without satisfactory explanation, notation as an adequate medium of music was brusquely rejected by Aristoxenus. Background in Music Technology and Signal Processing. Besides the thought-provoking fact that signal processing as the foundation of modern music technology itself originates from the domain of harmonic analysis and, similarly, became relevant to ̔musicology proper’ only by extension with a discrete agency purely logic in nature—i.e. the computer—now, real-time pitch-tracking and pitch-shifting can be used to augment ancient instruments electronically in order to pose archaeological questions and challenge sedimented hermeneutical interpretations. Aims. While re-enacting historical configurations, applied media theory provides an unconventional framework to interlink both backgrounds anachronistically. In practice, the aim of the present interdisciplinary approach is to take issue with common exegeses of the rise of ancient Greek music theory, deliver testable hypotheses to corroborate a modified picture and finally to overcome the outdated antithesis of Pythagorean vs. Aristoxenian views on music—i.e. numerology vs. phenomenology— propounded since the Hellenistic Period and still prevalent today. Main contribution. The historical background and epistemological circumstances that led to the formation of musicology as a separate field of knowledge are reviewed. During the course of discussion a "pre-Aristoxenian codec of notation" is uncovered and linked with scattered references to the barbiton-lyre. The acoustical significance of its origin becomes ̔instrumental’ to augment a self-made reconstruction of such an instrument electronically. Hereby a perceptual model of melody is re-enacted that logically connects and unifies theoretical camps previously considered irreconcilable. The technology and methodology necessary to achieve this is described. Implications. Towards the end of the 5th century, many sources ascribe a revolutionary ̔new music’ to the advent of frequent modulations and different ̔styles’ of playing techniques. Taking this revolution seriously, the present paper constructs a history of hearing that proposes a rupture in the ancient Greek sonosphere. Accordingly, the changed strategy of listening is regarded the true cause of the Aristoxenian separation of musicology. Today, the ̔kernel’ of this parting can be identified with the more general domain of "time-critical processes" in computation and signal processing whose application enables us to understand the subsequent reshaping of music theory and the radical remodelling of its philosophical conception. By extension, this lesson in mousikḗ may make us rethink music as still a vital epistemological field and may encourage us to form a new research domain possibly called computational archaeomusicology.